2021
DOI: 10.21873/invivo.12528
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Barrier Biomarker ZO1 and Endotoxin Are Increased in Blood of Patients With COVID-19-associated Pneumonia

Abstract: Background/Aim: The present study was undertaken to investigate (i) whether hospitalized patients with COVID-19 pneumonia present intestinal barrier dysfunction with consequent translocation of endotoxin into the systemic circulation and (ii) whether intestinal barrier biomarkers have any prognostic role in terms of progression to severe respiratory failure. Patients and Methods: In this prospective study, 22 patients with COVID-19-associated pneumonia and 19 patients with non-COVID-19-related community-acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Assimakopoulos et al showed that SARS-CoV-2 pneumonia is associated with an increase in the concentration of endotoxins and ZO-1 in serum, which indicates a dysfunction of the intestinal barrier. Additionally, a positive correlation was found between the level of endotoxin and the concentration of CRP and ferritin [ 102 ]. Moreover, Prasad et al presented a relationship between COVID-19 and disturbances in the microbiota, and the tightness of the intestinal barrier.…”
Section: Intestinal Infections and Antibiotic Therapymentioning
confidence: 99%
“…Assimakopoulos et al showed that SARS-CoV-2 pneumonia is associated with an increase in the concentration of endotoxins and ZO-1 in serum, which indicates a dysfunction of the intestinal barrier. Additionally, a positive correlation was found between the level of endotoxin and the concentration of CRP and ferritin [ 102 ]. Moreover, Prasad et al presented a relationship between COVID-19 and disturbances in the microbiota, and the tightness of the intestinal barrier.…”
Section: Intestinal Infections and Antibiotic Therapymentioning
confidence: 99%
“…Endotoxemia was also observed in 75% of 92 critically ill patients with COVID-19, with only two patients having positive blood cultures for Gram-negative organisms [90]. Significant endotoxemia was found in a cohort of 22 patients with COVID-19-related pneumonia, together with increased serum zonula occludens-1 levels, a marker of the integrity of the intestinal paracellular barrier, implying that there was intestinal barrier dysfunction and supporting the speculation that bacterial translocation from the gastrointestinal tract may complicate severe COVID-19 and may contribute to the cytokine storm [88,91]. In another study, the co-existence of low-grade endotoxemia with enhanced levels of zonulin in patients with COVID-19 was observed, as well as an association with thrombotic events [92].…”
Section: Covid-19 and Endotoxemiamentioning
confidence: 81%
“…In a recently published study, we have shown that patients with COVID-19-associated pneumonia have significantly higher serum ZO-1 concentrations as compared to healthy controls and this is associated with endotoxin translocation [ 44 ]. ZO-1 is a 210–225 kDa phosphoprotein that interacts with (i) the TJ proteins occludin, claudins and junctional adhesion molecule, (ii) molecular components of the intracellular tight junctional plaque such as ZO-2, ZO-3, afadin-6, cingulin and (iii) the actin cytoskeleton [ 9 ].…”
Section: Sars-cov-2 Infection and The Intestinal Barriermentioning
confidence: 99%